Green conversion of red snapper fish scale-derived carbon dots and its absorption properties for solar thermal desalination - Pandara, Dolfie Paulus; Tamuntuan, Gerald Hendrik; Bobanto, Maria Daurina; Ferdy, Ferdy (International Journal of Advances in Applied Sciences, 2024)
Fisheries wastes have been used as precursors for the synthesis of carbon dots (CDs). These wastes are often converted using hydrothermal methods which require high temperature and pressure, leading to high production costs, especially for large-scale production. This study aims to innovate a low-cost synthesis method with the potential for large-scale production. Green conversion of CDs from red snapper fish scale waste was carried out using a combination of immersion method and ultrasonic wave treatment. The results showed that the products had an absorption peak at a wavelength of 404 nm and an energy bandgap of 2.7 eV. Excitation at 404 nm was associated with non-bonding n orbital to antibonding orbital ?* electronic transitions due to the presence of free electron pairs and related with carbon-nitrogen (C-N) bonds. The 2.7 eV energy bandgap was associated with the state of amine groups containing free electron pairs located on the surface of CDs as well as blue light emission at a wavelength of 460 nm when CDs were illuminated with ultraviolet light. Red snapper fish scale-derived CDs showed fluorescence characteristics and the presence of nitrogen elements, making them potential photothermal materials for solar-powered seawater desalination processes.